Equilibrium composition variation of Q-phase precipitates in aluminum alloys. (1st October 2017) - Bobel, Andrew; Kim, Kyoungdoc; Wolverton, Christopher; Walker, Mike; Olson, Gregory B.
Abstract: Q-phase precipitation strengthened aluminum alloys have increasing interest in the automotive sector as a means of enabling higher operating temperatures and improved fuel economy. To enable the optimized design of Q-phase strengthened alloys, knowledge of precipitate composition variations is crucial. Here we use atom-probe tomography (APT) and transmission electron microscopy (TEM) to uncover the near equilibrium compositions of Q-phase precipitates in nine Al-Si-Mg-(Cu) alloys aged for 24 h–1000 h at 473 K. The composition of the Q-phase has been found to vary with bulk alloy composition, particularly in regards to changes in both Cu and Mg content. This composition variation is in contradiction to the stoichiometric line compound Al5 Cu2 Mg8 Si6 typically found in commercially available CALPHAD databases. Our results reveal a common compositional connection between the rod-like Q-phase precipitates and the B′ variant of the β′-phase commonly found in the Cu free Al-Si-Mg system. The presence of small alloying additions of Cu determines stability of either the hexagonal Q-phase or cubic β-phase upon aging to equilibrium conditions. The energetics of Cu variation within the Q-phase has been evaluated using first-principles calculations and demonstrates that interstitial Cu atoms stabilize the metastable B′-phase and that the observed Q-phase composition variation from the ground-state is due to off-stoichiometries in the single-phase field. Our analysis provide new insight into the compositional variation of precipitates formed during aging, having implications on the intended application of the alloy, whether for room temperature applications or castings that may see elevated temperature exposure. Graphical abstract: Image 1